(untitled) (Eurasian Journal of Learning and Academic Teaching, 2022)
In the genre of batal, which is considered one of the main genres of fine art, it is said about the importance of the genre of portrait. Information is given about the harmony and educational importance of these two genres, its past, future and features, as well as its role and opportunities in educating young people in the system of continuous education, their outlook, the formation of all spiritual qualities.